Análise Combinatória: estudo de Permutação Caótica no Ensino Médio - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This study aims to present an analysis of Study Combinatorial - permutation Chaotic through mathematical modeling as a strategy in the rescue of a significant teaching mathematics in high school . Therefore, we present permutation Chaotic as a problem situation modeled with regard to trend analysis and forecasting of results of an experiment . Thus prepared a proposal of class for students of basic and secondary education in which are carried out activities so that students know permutation Chaotic , learn to use it and apply it in various types of problem situations involving a other disciplines such as Biology, Chemical and Portuguese. The main objectives of this class , the material and the time needed and the prerequisites for its success will also be detailed in this work .
Keywords: Permutação Caótica; Análise Combinatória; Modelagem Matemática; Ensino- Aprendizagem - Matemática; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA